Development of magnetic imaging system for shape identification based on GMR sensor array - Roslan, Muhammad Kamil (2016)
Non-Destructive Evaluation (NDE) is one of the most common methodologies used in the industries. This method is proposed to examine the properties of ferromagnetic materials. NDE technique carries the ability to perform shapes evaluation of ferrous objects without permanently altering its characteristics. The NDE technique used in this study for shapes evaluation is based on the magnetization characteristics of ferrous metal specimens. In NDT industries measurement time is a key feature. Therefore, using a single small sized Giant Magneto Resistance (GMR) sensor element to scan an object in a fine grid is in most cases not practicable. Alternatively, a sensor array housing several tens of simultaneously operating elements is more reasonable. In this study, it presents the performance study of an array lining up 21 pieces of GMR sensor developed for evaluating shapes of ferrous metal specimens.